PENGARUH KINERJA EKONOMI, INVESTASI DAN UPAH TERHADAP PENYERAPAN TENAGA KERJA SEKTOR PERTANIAN DI INDONESIA - Belmondo, Berryl; Triani, Mike (Jurnal Kajian Ekonomi dan Pembangunan, 2020)
Abstract : This study aims to analyze the effect of (1) performance on labor absorption inthe agricultural sector in Indonesia. (2) investment in the absorption of labor in theagricultural sector in Indonesia. (3) agricultural sector labor wages in Indonesia. (4)jointly influence the economic performance, investment and labor wages in theagricultural sector in Indonesia. This type of research is descriptive and associativeresearch. The type of data used is panel data for 2011-2018 in 34 provinces in Indonesia.The analysis method used is the panel data method with the selected panel regressionmodel, namely the Fixed Effect Model (FEM.) The results of the study show that: (1)performance has a positive and significant effect on labor absorption in the agriculturalsector in Indonesia (2) investment has a negative and significant effect the absorption oflabor in the agricultural sector in Indonesia. (3) wages have a positive and significanteffect on employment in the agricultural sector in Indonesia. Taken together, economicperformance, investment and have a significant effect on employment in the agriculturalsector in Indonesia.Keywords: Agricultural Sector Labor Absorption, Economic Performance, Investment,Wage.